Rosemary's baby [videorecording (DVD)] - Polanski, Roman; Polanski, Roman; Castle, William; Farrow, Mia, 1945-; Cassavetes, John, 1929-1989; Gordon, Ruth, 1896-1985; Blackmer, Sidney, 1895-1973; Komeda, Krzysztof; Levin, Ira, 1929-2007 (Criterion collection, 2012)
Based on Ira Levin's bestselling novel, Mia Farrow plays "a young mother-to-be who grows increasingly suspicious that her over-friendly elderly neighbors and self-involved actor husband are hatching a satanic plot against her and her baby."